Socio-Psychological Characteristics of Subjective Well-Being among Students - Hakobyan, Naira; Sotnyk, Iryna; Khachatryan, Anna (ՀՀ ԳԱԱ)
The problem of a person’s subjective well-being is one of the fundamental issues studied by various sciences, such as philosophy, economics, medicine, and psychology. Each science complements this concept with its own content. Medicine connects subjective well-being with other components of the quality of life, such as mental health. Currently, this problem is actively studied by psychologists. This is due to the need to understand the mechanisms underlying subjective well-being: how these mechanisms regulate a person’s behaviour and how they affect their relationships with other people. The problem of subjective well-being is associated with the problem of positive development of personal growth. Scientists show considerable interest in this problem, taking into account the trends in the development of modern society. Subjective well-being is understood as a state of mental health, coherence of mental processes and internal harmony, which depends on whether a person has clear goals, as well as the resources and conditions for achieving them. Subjective well-being of students is one of the current problems of psychological science, which acquires special significance in the modern educational and socio-cultural environment. It is considered a multi-component phenomenon, the basis of which is a person’s subjective experiences, internal adaptability, and the ability to function effectively in the social environment. Անձի սուբյեկտիվ բարեկեցության խնդիրը հիմնարար խնդիրներից է, որն ուսումնասիրվում է տարբեր գիտությունների կողմից, ինչպիսիք են փիլիսոփայությունը, տնտեսագիտությունը, բժշկությունը և հոգեբանությունը: Յուրաքանչյուր գիտություն լրացնում է այս հասկացությունը հատուկ բովանդակությամբ: Բժշկությունը սուբյեկտիվ բարեկեցությունը կապում է կյանքի որակի, հոգեկան առողջության այլ բաղադրիչների հետ: Ներկայումս այս խնդիրն ակտիվորեն ուսումնասիրվում է հոգեբանների կողմից: Դա պայմանավորված է սուբյեկտիվ բարեկեցության հիմքում ընկած մեխանիզմները հասկանալու անհրաժեշտությամբ. թե ինչպես են այդ մեխանիզմները կարգավորում մարդու վարքագիծը և ինչպես են ազդում նրա՝ այլ մարդկանց հետ հարաբերությունների վրա: Սուբյեկտիվ բարեկեցության խնդիրը կապված է անձնային աճի պոզիտիվ զարգացման խնդրի հետ: Գիտնականները զգալի հետաքրքրություն են ցուցաբերում այս խնդրի նկատմամբ՝ հաշվի առնելով ժամանակակից հասարակության զարգացման միտումները: Սուբյեկտիվ բարեկեցությունը հասկացվում է որպես հոգեկան առողջության, հոգեկան գործընթացների համահունչության և ներքին ներդաշնակության հոգեվիճակ, որը կախված է նրանից, թե արդյոք անձն ունի հստակ նպատակներ, դրանց հասնելու ռեսուրսներ և պայմաններ: Ուսանողների սուբյեկտիվ բարեկեցությունը հոգեբանական գիտության արդիական խնդիրներից մեկն է, որը հատուկ նշանակություն է ստանում ժամանակակից կրթական և սոցիալ-մշակութային միջավայրում: Այն համարվում է որպես բազմաբաղադրիչ երևույթ, որի հիմքում ընկած են անձի սուբյեկտիվ փորձառությունները, ներքին հարմարվողականությունը և սոցիալական միջավայրում արդյունավետ գործելու ունակությունը։
Keywords: Psychology